2020
DOI: 10.1177/0268355520953317
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the calibre and length of needle on the stability of sclerosing foam

Abstract: Objectives Little is known how calibre and length of needles affect the stability of sclerosing foam. Methods Foams were made of 0.5%, 1%, 2% and 3% polidocanol, and 0.2%, 0.5%, 1% and 3% sodium tetradecyl sulfate (STS), which were mixed with air in the proportion of 4:1. These foams were ejected through needles with the length of: 4 mm, 6 mm and 13 mm, and diameter of: 0.26 mm, 0.3 mm and 0.4 mm. Results Foams made of more concentrated polidocanol were more stable. Regarding STS an opposite relationship was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Skuła et al ( 6 ) conducted a commendable study on the influence of needle caliber on foam stability, shedding light on the significant impact of needle caliber and length. A meticulous examination revealed that both the needle caliber and length play a role in determining foam stability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skuła et al ( 6 ) conducted a commendable study on the influence of needle caliber on foam stability, shedding light on the significant impact of needle caliber and length. A meticulous examination revealed that both the needle caliber and length play a role in determining foam stability.…”
Section: Discussionmentioning
confidence: 99%
“…Foam sclerotherapy is a safe and effective therapeutic option for hemorrhoids ( 4 ). In foam sclerotherapy, achieving a stable sclerosant foam for optimal results is crucial because poor foam stability can potentially result in serious complications ( 5 , 6 ). Blisters, paradoxical embolism, orbital compartment syndrome, and transient weakness of the facial nerve branch are complications that can arise when treating head and neck VMs ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 In foam sclerotherapy, achieving stable sclerosant foam is crucial for optimal results, as poor foam stability can lead to serious complications. 4,5 To achieve improved therapeutic outcomes, it is necessary to attain the utmost stability of the sclerosant foam. 6 The most commonly used technique to create sclerosant foam is the Tessari method, in which the agent is combined with air.…”
mentioning
confidence: 99%